Effect of urban vs. rural residence on the association between atopy and wheeze in Latin America: findings from a case–control analysis. Issue 2 (February 2015) - Endara, P.; Vaca, M.; Platts‐Mills, T. A. E.; Workman, L.; Chico, M. E.; Barreto, M. L.; Rodrigues, L. C.; Cooper, P. J.
Summary Background The association between atopy and asthma is attenuated in non‐affluent populations, an effect that may be explained by childhood infections such as geohelminths. Objective To investigate the association between atopy and wheeze in schoolchildren living in urban and rural areas of Ecuador and examine the effects of geohelminths on this association. Methods We performed nested case–control studies among comparable populations of schoolchildren living in rural communities and urban neighbourhoods in the Province of Esmeraldas, Ecuador. We detected geohelminths in stool samples, measured recent wheeze and environmental exposures by parental questionnaire, and atopy by specific IgE (sIgE) and skin prick test (SPT) reactivity to aeroallergens. Results Atopy, particularly sIgE to house dust mite (HDM), was more strongly associated with recent wheeze in urban than rural schoolchildren: (urban, adj. OR 5.19, 95% CI 3.37–8.00, P < 0.0001; rural, adj. OR 1.81, 95%CI 1.09–2.99, P = 0.02; interaction, P < 0.001). The population fractions of wheeze attributable to atopy were approximately two‐fold greater in urban schoolchildren: SPT to any allergen (urban 23.5% vs. rural 10.1%), SPT to HDM (urban 18.5% vs. rural 9.6%), and anti‐HDM IgE (urban 26.5% vs. rural 10.5%), while anti‐Ascaris IgE was related to wheeze in a high proportion of rural (49.7%) and urban (35.4%) children. The association between atopy and recent wheeze was attenuated by markers of geohelminth infections. Conclusions Our data suggest that urban residence modifies the association between HDM atopy and recent wheeze, and this effect is explained partly by geohelminth infections.